Principles of designing lesson plans for teaching ESL or EFL - Nosirova Nodira Nodirovna; Pulatova Mohichehra Temirovna (Genius Journals, 2022)
The article considers the principles of designing lesson plans for teaching ESL or EFL.
Keywords: lesson plan; presentation; concept